Subsystem of positioning the actuator for an electronic diesel control syste - Prokhorenko, Andriy; Samoilenko, Dmytro; Orlinski, Piotr; Bednarski, Mateusz; Kravchenko, Serhii; Karyagin, Igor (Łukasiewicz Instytut Technologii Eksploatacji, 2018)
The authors proposed the concept of the synthesis of the algorithm for the electronic diesel controller (EDC), based on the analogy with the operation of a mechanical spring-lever governor of direct action. The system of automatic positioning using HEINZMANN StG 6-02V actuator is developed and practically implemented. A preliminary tuning of the electronic PID controller was performed, which ensured the operation of the actuator with a-periodic transients at a high speed. The present work is a part of the project on the creation of an electronically controlled fuel delivery system for the transport diesel.
Keywords: diesel; fuel delivery system; high pressure fuel pump; electronic control; actuator; microcontroller; PID controller